HUBUNGAN ANTARA PERHATIAN ORANG TUA DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR SISWA KELAS X JURUSAN ADMINISTRASI PERKANTORAN SMK BATIK 2 SURAKARTA - Hadi, Sofwan; Mardayanti, Mella (Jurnal Pendidikan : Riset dan Konseptual, 2021)
Parental attention and student motivation, related to student achievement. Where students are getting the attention of parents and their motivation to learn is high, the better the student's learning achievement. But the problem is not all students get the attention of parents and also motivation to learn. This happened in class X Department of Office Administration of SMK Batik 2 Surakarta in the training year of 2010/2011. 2010/2011, to find out whether or not there was a significant relationship between learning motivation and student achievement in class X Department of Office Administration at SMK Batik 2 Surakarta in the 2010/2011 training year, and to find out whether there was a significant relationship between parents' attention and learning motivation with class X student learning achievement Department of Office Administration Batik Vocational High School 2 Surakarta in 2010/2011 training. This type of research used by researchers in this research is quantitative research with descriptive methods. Where data collection techniques using questionnaires or questionnaires and supported by the documentation method. The population in this study were students of class X Department of Office Administration at SMK Batik 2 Surakarta in the 2010/2011 training year. The sampling technique used in this study was proportional random sampling, as many as 95 students or 60% of the total population. The sample used was 57 students. By using the results of the analysis of multiple linear lines. The conclusions of this research are: (1) There is a significant relationship between parents' attention and the learning achievement of Grade X students of the Department of Office Administration at SMK Batik 2 Surakarta in the training year 2010/2011. (Price tcount> t table or 3.076> 1.673 with a significance level of 5%). (2) There is a significant relationship between learning motivation and student achievement in class X Department of Office Administration at SMK Batik 2 Surakarta in the training year 2010/2011. (Price tcount> t table or 4.143> 1.673 at the 5% significance level). (3) There is a significant relationship between parents' attention and learning motivation with student achievement in class X Department of Office Administration at SMK Batik 2 Surakarta in the training year 2010/2011. (Price Fcount> F table or 18.156> 3.162 at the 5% significance level). Double linear line equation Å¶ = 46.116 + 0.241 X1 + 0.251 X2.